Dietary Macronutrient Distribution and Nutrition-Related Outcomes in Cystic Fibrosis: A Systematic Review (P12-016-19). (13th June 2019) - Rozga, Mary; Alvarez, Jessica; Bowser, Ellen; Bailey, Julianna; Farnham, Kristen; McDonald, Catherine; Mangus, Mark; Porco, Kat; Padula, Laura
Abstract: Objectives: Conduct a systematic review (SR) to determine the relationship between dietary macronutrient distribution and nutrition-related outcomes in pediatric and adult participants with cystic fibrosis (CF). Methods: A literature search of Medline, CINAHL and Embase databases was conducted to identify peer-reviewed articles published from January 2002- May 2018 that examined human participants with CF and addressed the research objective. Articles were screened for relevance, data was extracted and summarized, and risk of bias was assessed by a multidisciplinary team of researchers, practitioners, patient advocates and SR methodologists. Results: A total of 2409 articles were identified in the search and eight cross-sectional studies and one case-control study met inclusion criteria ( N = 4 in pediatrics, N = 4 in adults, N = 1 combined). Evidence quality was low due to weak study designs, small samples size and inconsistent outcome reporting. Available studies did not show statistically significant relationships between dietary macronutrient distribution and lung function (FEV1%) (3 studies) when estimated protein intake ranged from 10–23% of energy, fat intake from 20–46% of energy and carbohydrate intake from 32–67% of energy. Macronutrient distribution was not significantly associated with anthropometric measurements/growth (3 studies), gastrointestinal symptoms (2 studies), glucose fluctuations (1 study) or lipid profile (1 study) in this SR. There were no studies identified examining the relationship between macronutrient distribution and mortality or Quality of Life. Meta-analysis was not possible due to the low quality of data reported. Conclusions: Recent evidence describing the relationship between dietary macronutrient distribution and nutrition-related outcomes in participants with CF is sparse and low in quality. The evidence reviewed does not suggest that dietary macronutrient distribution is related to key clinical CF outcomes. Higher-quality trials and longitudinal studies are needed to confirm these findings. The need for updated dietary studies is particularly important in light of recent therapeutic advances that are changing the clinical course of individuals with CF. Funding Sources: Academy of Nutrition and Dietetics and the Medical Nutrition Practice Group DPG.